2023
DOI: 10.3389/fmicb.2023.1106643
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the noncoding RNA regulatory networks of H37Rv- and H37Rv△1759c-infected macrophages

Abstract: Noncoding RNAs regulate the process of Mycobacterium tuberculosis (M. tb) infecting the host, but there is no simultaneous transcriptional information of long non-coding RNAs (lncRNAs) and circular RNAs (circRNAs) and the global regulatory networks of non-coding RNA. Rv1759c, a virulence factor, is a member of protein family containing the proline-glutamic acid (PE) in M. tb, which can increase M. tb survival. To reveal the noncoding RNA regulatory networks and the effect of Rv1759c on non-coding RNA expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 107 publications
0
1
0
Order By: Relevance
“…Recent evidence suggested that circRNAs have been recognized as regulatory molecules involved in the development and progression of a range of human diseases, including tuberculosis. In tuberculosis, circRNAs have been shown to modulate host anti-tuberculosis immune responses, such as reducing cell apoptosis and regulating autophagy 15 17 . A previous study identified 142 circRNAs that were aberrantly expressed in tuberculosis patients, 32 upregulated and 110 downregulated, which implied a potential role of circRNAs for diagnosing tuberculosis.…”
Section: Introductionmentioning
confidence: 99%
“…Recent evidence suggested that circRNAs have been recognized as regulatory molecules involved in the development and progression of a range of human diseases, including tuberculosis. In tuberculosis, circRNAs have been shown to modulate host anti-tuberculosis immune responses, such as reducing cell apoptosis and regulating autophagy 15 17 . A previous study identified 142 circRNAs that were aberrantly expressed in tuberculosis patients, 32 upregulated and 110 downregulated, which implied a potential role of circRNAs for diagnosing tuberculosis.…”
Section: Introductionmentioning
confidence: 99%